Distinct histopathological phenotypes of severe alcoholic hepatitis suggest different mechanisms driving liver injury and failure - Jing Ma; Adrien Guillot; Zhihong Yang; Bryan Mackowiak; Seonghwan Hwang; Ogyi Park; Brandon J. Peiffer; Ali Reza Ahmadi; Luma Melo; Praveen Kusumanchi; Nazmul Huda; Romil Saxena; et al. (The Journal of Clinical Investigation, 2022)
Intrahepatic neutrophil infiltration has been implicated in severe alcoholic hepatitis (SAH) pathogenesis; however, the mechanism underlying neutrophil-induced injury in SAH remains obscure. This translational study aims to describe the patterns of intrahepatic neutrophil infiltration and its involvement in SAH pathogenesis. Immunohistochemistry analyses of explanted livers identified two SAH phenotypes despite a similar clinical presentation, one with high intrahepatic neutrophils (Neuhi), but low levels of CD8+ T cells, and vice versa. RNA-Seq analyses demonstrated that neutrophil cytosolic factor 1 (NCF1), a key factor in controlling neutrophilic ROS production, was upregulated and correlated with hepatic inflammation and disease progression. To study specifically the mechanisms related to Neuhi in AH patients and liver injury, we used the mouse model of chronic-plus-binge ethanol feeding and found that myeloid-specific deletion of the Ncf1 gene abolished ethanol-induced hepatic inflammation and steatosis. RNA-Seq analysis and the data from experimental models revealed that neutrophilic NCF1-dependent ROS promoted alcoholic hepatitis (AH) by inhibiting AMP-activated protein kinase (a key regulator of lipid metabolism) and microRNA-223 (a key antiinflammatory and antifibrotic microRNA). In conclusion, two distinct histopathological phenotypes based on liver immune phenotyping are observed in SAH patients, suggesting a separate mechanism driving liver injury and/or failure in these patients.